The TCO concept in German forensic homicide offenders with schizophrenia spectrum disorders – new findings from a file-based, retrospective cross-sectional study - Findeis, Hannelore; Strauß, Maria; Kröber, Hans-Ludwig (Frontiers in Psychiatry, 2024)
There is evidence that there is a small group of people with schizophrenia spectrum disorders who are more likely to commit homicide than those in the general population. However, there is limited knowledge about the psychopathology that leads to homicide in this group. The aim of this study was to examine two commonly used definitions of the Threat/Control-Override (TCO) concept, which aims to identify a certain risk of serious violence in patients with schizophrenia spectrum disorders. Methods. This is a sub analysis of a file-based, retrospective and exploratory cross-sectional study. All forensic homicide offenders with schizophrenia spectrum disorders who were detained at the Forensic Hospital Berlin as of 31 December 2014 were examined for the occurrence of TCO according to two commonly used definitions. Results. Of a total of 419 forensic patients with schizophrenia spectrum disorders, 78 committed homicide (18.6 %). The forensic homicide offenders with schizophrenia spectrum disorders were characterised by being male, unemployed, single and having committed (attempted) manslaughter. Irrespective of the definition used, the entire TCO complex was present in less than a third of the sample. In both definitions, Threat symptoms were slightly less frequent than Control-Override symptoms. While Threat symptoms occurred less frequently in Stompe et al.'s definition, Control-Override symptoms were the most common. With regard to Kröber's (2008) definition of Threat and Control-Override, the situation is exactly the opposite. Discussion. Regarding the entire TCO complex, Kröber's definition seems a little more open and Stompe et al.'s more strict (38.5 % vs. 35.9 %). Since TCO only occurs in about one third of the subjects in both definitions, neither definition appears to be conclusive. A combination with proportions from both definitions could be a contribution to a future definition of TCO. The present study provides scarcely published primary data on psychopathology in homicide offenders with schizophrenia spectrum disorders, especially on the much discussed TCO concept in two definitions.In order to determine the most useful definition of TCO, to avoid false positives and to identify clear psychopathological risk symptoms, larger samples and comparative studies with offenders and nonoffenders should be conducted in the future.